The Prosecution of State-Level Human Trafficking Cases in the United States - Farrell, Amy; DeLateur, Monica J; Owens, Colleen; Fahy, Stephanie (Anti-Trafficking Review, 2016)
In an effort to combat human trafficking, the United States federal government and all fifty states passed new laws that criminalise human trafficking and support the identification and prosecution of human trafficking perpetrators. Despite the passage of these laws, only a small number of human trafficking cases have been prosecuted in the last fifteen years. Guided by the notion that prosecutors seek to avoid uncertainty when making decisions to pursue criminal prosecution, we explore how human trafficking crimes are indicted under these newly defined state laws. Using a sample of cases from twelve US counties and interviews with police, prosecutors and court personnel, we examine the factors that influence the decision to prosecute crimes investigated as human trafficking in state court. This research informs our understanding of why so few human trafficking cases are prosecuted and why human trafficking suspects are rarely convicted of trafficking offenses.